Influence of different Rhizobium sullae strains and soil fertility on the agronomic performance of Sulla (Sulla coronaria L.) - Sitzia M.; Salis L.; Dettori I.; Sara G.; Loi A.; Yates R.J.; Garau G. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Sulla is widely used as a forage legume in several Mediterranean regions, however only a limited area of Sardinia is cultivated to Sulla. Its cultivation is mainly confined to areas where its native specific rhizobium is available and soil pH is alkaline. Four farms were selected in the southern part of Sardinia with slightly acid soils and where the Sulla had never been sown. Intensive and large-scale trials were conducted to assess the adaptation of Sulla to different soil types and to assess the effectiveness of a range of elite Sulla rhizobial strains. The un-inoculated control treatments had significantly lower nodule numbers at all sites, indicating the presence of a very low Sulla rhizobial background and stressing the importance to inoculate Sulla in the region. Some of the paddocks had a challenging fertility for the growth of Sulla; however the use of an effective and robust rhizobial strain such us WSM1592 and 79N2 was of paramount importance to successful growth the species.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)